Evaluation of second line and subsequent targeted therapies in metastatic renal cell cancer (mRCC) patients treated with first line cediranib - Richter, Suzanne; Seah, Jo-An; Pond, Gregory R; Gan, Hui K; Mackenzie, Mary J.; Hotte, Sebastien J.; Mukherjee, Som D.; Murray, Nevin; Kollmannsberger, Christian; Heng, Daniel; et al. (Canadian Urological Association Journal, 2014)
Introduction: Pivotal phase III trials have positioned angiogenesis inhibitors as first-line therapy for the management of most advanced or metastatic renal cell carcinomas (mRCC). Approaches to second-line therapy, however, remain more controversial with respect to drug selection and drug sequencing. Methods: In this study we evaluated mRCC patients who were initially treated on the first-line National Cancer Institute (NCI) trial with the highly potent vascular endothelial growth factor receptor tyrosine kinase inhibitor (TKI), cediranib, to determine the efficacy and tolerability of subsequent therapies. Results: Twenty-eight (65.1%) of the 43 patients enrolled on the first-line cediranib trial were known to receive second-line therapy, most commonly sunitinib (n = 21), with 4 (14%), 2 (7%) and 1 (3%) patients receiving temsirolimus, sorafenib, and interleukin, respectively. Of these, 14 (50%) went on to have 3 or more lines of therapy. The progression-free survival (PFS) proportion (PFS) at 1 year from starting second line was 30% (14.5%–47.9%). Longer duration of first-line cediranib treatment was modestly associated with longer duration of second-line treatment (Spearman rho 0.26). Patients who discontinued cediranib for toxicity were less likely to receive second-line sunitinib. Conclusion: In this real world evaluation, sequential use of TKIs for the management of mRCC was common. PFS with sequential TKIs was similar to observed and published results for any second-line therapy. Prior toxicity affected treatment patterns and the frequent use of at least 3 lines of therapy underscores the need for prospective sequencing trials in this disease.